Kekuatan tarik logam hasil pengelasan dengan las listrik dan las LPG - Jefta Ratela; Jozua Huwae; Marinus Tappy; Raman Simanjuntak; Lexy Hosang; Novie Wijaya (JURNAL BLUEFIN FISHERIES, 2019)
Steel welding, especially soft steel with carbon content ranging from 0.3%, which is installed in the construction of fishing vessels, often using various types of electrodes including kobe steel RB, 26 Niko steel RD 260 Esap steel OK 46,64, Philips steel PH 68 JIS D 4314, AWS E 6013 and others, while LPG Las only uses bait welding from welding wire with a size of 3-5 mm. The purpose of this study is to examine the tensile strength of metal welding results between welds of Electricity with LPG Welding. The variable observed in this study is the amount of tensile strength in two types of electric welding machines and LPG welding. From the data obtained from the test results, then the magnitude of the tensile strength is sought by distributing the results of observations with cross sections of test specimens used in the form of stretch loads, mouth strength, maximum load, maximum tensile strength, broken load and elastic modulus. From the results of the tensile testing performed, it turns out that there is a difference in the welding power of Electric with LPG Gas welding where the electric welding strength is greater than the welding strength of LPG Gas. The electric weld tensile strength is 69.13 Kgf / mm² and LPG Gas welding is 26.20 Kgf / mm²